2018
DOI: 10.3390/nu10040453
|View full text |Cite
|
Sign up to set email alerts
|

Fairness-Based Tasks for Assessing Children’s Perceptions of Food Quantities and Associations with Portion Selection

Abstract: It is critical to develop ecologically valid experimental methods to assess consumers’ food-related behaviors. Ad libitum approaches are often used but may not be appropriate for studies with children or with products that are not typically consumed until the individual feels full. The current study presents novel methods to assess children’s size perception and portion preference for gummy candies. In the first study, 62 children (30 boys, 32 girls) aged 6 to 9 years completed two matching tasks: one using pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In the United Kingdom and Ireland, childhood obesity prevention campaigns have identified serving size as a key issue in preventing child obesity and have emphasized the importance of offering appropriately sized food to children [43,44]. Ferrage et al also suggested that because there is no association between the serving sizes of snacks and the portion selection among young children, reducing the size of snacks may be an effective strategy when providing snacks for young children [45]. In the future, it could be considered that stipulate different serving sizes for children food should be established.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom and Ireland, childhood obesity prevention campaigns have identified serving size as a key issue in preventing child obesity and have emphasized the importance of offering appropriately sized food to children [43,44]. Ferrage et al also suggested that because there is no association between the serving sizes of snacks and the portion selection among young children, reducing the size of snacks may be an effective strategy when providing snacks for young children [45]. In the future, it could be considered that stipulate different serving sizes for children food should be established.…”
Section: Discussionmentioning
confidence: 99%
“…This would provide a more granular measure and avoid potential floor or ceiling effects. Future research should also examine apportionable foods [43] or foods sold in small pre-cut portions, such as candies, for which it is the number of units rather than the portion size that drives portion size perception and preferences (for example: [44]). Similarly, investigating the role of the shape of the portions could be interesting.…”
Section: Discussionmentioning
confidence: 99%